Sonic Hedgehog signaling in the development of the mouse hypothalamus - Blaess, Sandra; Szabó, Nora; Haddad-Tóvolli, Roberta; Zhou, Xunlei; Alvarez-Bolado, Gonzalo (Frontiers in neuroanatomy, 2015)
The expression pattern of Sonic Hedgehog (Shh) in the developing hypothalamus changes over time. Shh is initially expressed in the prechordal mesoderm and later in the hypothalamic neuroepithelium-- first medially, and then in two off-medial domains. This dynamic expression suggests that Shh might regulate several aspects of hypothalamic development. To gain insight into them, lineage tracing, (conditional) gene inactivation in mouse, in ovo loss- and gain-of-function approaches in chick and analysis of Shh expression regulation have been employed. We will focus on mouse studies and refer to chick and fish when appropriate to clarify. These studies show that Shh-expressing neuroepithelial cells serve as a signaling center for neighboring precursors, and give rise to most of the basal hypothalamus (tuberal and mammillary regions). Shh signaling is initially essential for hypothalamic induction. Later, Shh signaling from the neuroepithelium controls specification of the lateral hypothalamic area and growth-patterning coordination in the basal hypothalamus. To further elucidate the role of Shh in hypothalamic development, it will be essential to understand how Shh regulates the downstream Gli transcription factors.